Solar Distillation Experiment Parabolic Dish Integrated with Spiral Copper Tube Condenser - Kurniawan, Wahyu; Amin, Muhammad; A. Abdullah, Nasruddin (Fakultas Teknik Universitas Samudra, 2025)
The availability of clean water has become a major challenge due to population growth and climate change, despite 97.5% of the Earth's surface consisting of water, only 2.5% is suitable for consumption. Desalination has become an important solution to convert seawater into fresh water. One of the technologies used is the parabolic solar concentrator, which focuses sunlight to a single point to generate steam. Research using a parabola measuring 71.98 cm × 50 cm with a focal point of 62 cm produced 0.88 liters of distilled water with a cooler and 0.23 liters without a cooler. The efficiency increased from 11% to 12.5% with the use of a cooler. Spiral tubes also help to reduce the temperature of the outgoing steam, enhancing the effectiveness of the system.